Iptek bagi Masyarakat Kelompok Pembudidaya Rumput Laut di Desa Labuhan Sangoro yang Mengalami Kendala Ketersediaan Bibit - Neri Kautsari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Agar Maju and Balong Ate group is two of five groups of seaweed farmers at Labuhan Sangoro Village facing shortage of seeds quantitatively qualitatively. The project purpose seaweed seedling management then community assistance and training carried out from AprilNovember 2016. The results obtained indicate that the Balong Ate and Agar Maju group has know of management of seaweed seed garden. Amount of the seaweed seed garden of each group is 40 x 40 m with tightrope number is 20 and each strap are 200 clumps. Observation of seaweed growth rate indicates that the seaweed has a very good growth rate with growth rate 3.21 g/day.